IPTEK BAGI MASYARAKAT (IBM) DUSUN LEBARI DAN DUSUN KRAJAN UNTUK PENGELOLAAN AIR BUANGAN RUMAH TANGGA - Siwiendrayanti, Arum; Pawenang, Eram Tunggul; Endroyo, Bambang (Rekayasa : Jurnal Penerapan Teknologi dan Pembelajaran, 2015)
Domestic wastewater of Lebari Sub-village and Krajan Sub-village was disposed so unproperly that it overflowed onto surroundings. When the met garbage and livestock manure, it would attract flies and mice; and also contaminate the surrounding water. Pawenang (2010) riset showed that the spring water which flowed into Jaro River and Sronto River did not meet the bacteriological qualification because it had 1.100/100ml and >2.400/100ml total coliform number, whereas the limit was 10/100ml. Public Health Centre data showed that diarea always on the top three. Both non-physical and physical efforts were needed. The physical effort was done by building a comunal wastewater treatment. The non-physical efford was done with education about wastewater management and wastewater treatment maintenace. The public education increased knowladge rate of 83.3% mothers participants and 90% fathers participants. It had been already built 2 units of domestic wastewater treatment which covered 60 houses. It had been formed a wastewater superintendent forum which was well observed be properly able to manage and to maintain the wastewater treatment units.